Determining Critical Success Factors of Project Management in Allianz Life Indonesia - Sefrina Christy, Amalia; Firman, Aries F. (The Indonesian Journal of Business Administration, 2017)
Abstract - Allianz is one of the largest companies in the world which providing insurance services, banking and asset management. The company was originally founded in 1890 in Germany. “Project portfolio” represents the pool of projects at Allianz defined and approved by Board of Director (BoD) and managed centrally by the Central Project Office (CPO)/Project Management Office (PMO). All initiated projects are consolidated in one place regardless of department owner, business area, or project status. With respect to project lifecycle especially on system development, Allianz has its own methodology called Allianz Development Methodology (ADM). In the most cases, a successful project is based on three common criteria, which are cost, time, and quality. But in fact, evidence for success and failure of a project is not only seen on the accomplishments of cost, time, and quality. This research comes up to find out the indicators of success and failure project according to project manager, business user, and IT programmer perspectives in Allianz Life Indonesia in order to resolve the problem. Research methodology used to find out this research question is based on qualitative analysis. The data will be collected by interviewing nine persons, which reflect the stakeholders of Allianz Life Indonesia’s operation. When used along with quantitative methods, qualitative research can help us to interpret and better understand the complex reality of a given situation and the implications of quantitative data. Results from this study are expected to help Allianz Life Indonesia project management team to achieve specific project performance level. The key success factor of project management carried out at Allianz Life Indonesia is not only derived from technical factor but also related to non-technical factors in managing the work environment. Keywords: Allianz Development Methodology (ADM), Central Project Office (CPO), Project Management Office (PMO), Project Management, Critical Success Factor.